The vasopressin system: new insights for patients with kidney diseases: Epidemiological evidence and therapeutic perspectives. (14th September 2017) - Clark, W. F.; Devuyst, O.; Roussel, R.
Abstract: People with chronic kidney disease (CKD) are at risk of severe outcomes, such as end‐stage renal disease or cardiovascular disease, and CKD is a globally increasing health burden with a high personal and economic cost. Despite major progresses in prevention and therapeutics in last decades, research is still needed to reverse this epidemic trend. The regulation of water balance and the state of activation of the vasopressin system have emerged as factors tightly associated with kidney health, in the general population but also in specific conditions; among them, various stages of CKD, diabetes and autosomal dominant polycystic kidney disease (ADPKD). Basic science findings and also epidemiological evidence have justified important efforts towards interventional studies supporting causality, and opening therapeutic avenues. On the basis of recent clinical data, the blockade of V2 vasopressin receptors using tolvaptan in patients with rapidly progressing ADPKD has been granted in several countries, and a long‐term randomized trial evaluating the effect of an increase in water intake in patients with CKD is on‐going. Abstract : Content List ‐ Read more articles from the symposium: "Vasopressin: novel roles for an old hormone. Emerging therapies in cardiometabolic and renal diseases".